Evaluasi Tingkat Kebisingan Kawasan Selatan Universitas Negeri Padang - Vera Surtia Bachtiar; Reri Afrianita; Ary Zamzamy (Jurnal Dampak, 2018)
This study aims to determine and evaluate the level of noise in the southern area of Universitas Negeri Padang (UNP) Kampus Air Tawar conducted at 23 points of measurement with 16 outside outdoor points and 7 indoor measurement points. Method of measurement under regulation of Indonesian government, KepMenLH Regulation no. 48 thn 1996 which regulate the noise level standard by using SLM (Sound Level Meter). The highest outdoor noise level occurs in front of GOR UNP (S16) at the time of L3 which is 80,91 dBA, while the highest indoor noise level when there was activity as well as no activity in the room was happened in lecture hall FBSS UNP (S7-interior) with value equal to 83, 99 dBA and 64.65 dBA. All points of a total of 16 outdoor and 7 indoor measurement points exceed the standard noise level threshold which is 55 dBA (+3 dB tolerance). However, from the questionnaire results most respondents just feel slightly disturbed by outdoor noise in the study area. The noise control that can be done such as cultivate number of natural vegetation such as heliconia sp, tea, acacia tree and pringgodani bamboo, also the installation of continuous wall from type of clear fiber that serves as building noise absorbers.